Benzo-Fused 1,4-Heterocycles via Dialkyl Carbonate Chemistry - Musolino, Manuele; Aricò, Fabio (Synthesis, 2019)
A novel halogen-free synthesis of benzo-fused six-membered 1,4-heterocycles through the chemistry of dialkyl carbonates is reported. Commercially available catechol, 2-aminophenol, and 2-aminothiophenol were reacted first with ethylene carbonate in an autoclave to give O-hydroxyethyl, N-hydroxyethyl, and S-hydroxyethyl derivatives respectively, through a BAl2 mechanism. Then 2-(2-hydroxyethoxy)phenol and 2-(2-hydroxyethylamino)phenol were cyclized in excellent yields by reaction with dimethyl carbonate (DMC) and DABCO as a bicyclic organic base to give the corresponding benzodioxine and benzoxazine derivative, respectively. Moreover, 2-(2-aminophenylthio)ethanol afforded the benzothiazine derivative in good yield by reaction with DMC with an excess of a strong base such as NaH. The investigation on the cyclization reaction has highlighted that several equilibria are involved leading to the formation of carbonate and carbamate intermediates through BAc2 mechanisms. Depending on the reaction conditions employed, these intermediates may undergo either kinetic-controlled ring closure by a BAl2 mechanism or by-product formation.
Keywords: heteroycles; cyclization reaction; green chemistry; alkylation; chemoselectivity